Conjugation of Smt3 to Dorsal May Potentiate the Drosophila Immune Response - Bhaskar, Vinay (American Society for Microbiology, 2002)
A variety of transcription factors are targets for conjugation to the ubiquitin-like protein Smt3 (also called SUMO). While many such factors exhibit enhanced activity under conditions that favor conjugation, the mechanisms behind this enhancement are largely unknown. We previously showed that the Drosophila melanogaster rel family factor, Dorsal, is a substrate for Smt3 conjugation. The conjugation machinery was found to enhance Dorsal activity at least in part by counteracting the Cactus-mediated inhibition of Dorsal nuclear localization. In this report, we show that Smt3 conjugation occurs at a single site in Dorsal (lysine 382), requires just the Smt3-activating and -conjugating enzymes, and is reversed by the deconjugating enzyme Ulp1. Mutagenesis of the acceptor lysine eliminates the response of Dorsal to the conjugation machinery and results in enhanced levels of synergistic transcriptional activation. Thus, in addition to controlling Dorsal localization, Smt3 also appears to regulate Dorsal-mediated activation, perhaps by modulating an interaction with a negatively acting nuclear factor. Finally, since Dorsal contributes to innate immunity, we examined the role of Smt3 conjugation in the immune response. We find that the conjugation machinery is required for lipopolysaccharide-induced expression of antimicrobial peptides in cultured cells and larvae, suggesting that Smt3 regulates Dorsal function in vivo.